BLACK WOMAN IN THE SPORTS WORKING MARKET: SOME CONSIDERATIONS (Fiep Bulletin - online, 2015)
When we think about the situation of the black woman in Brazil, we have to take many things into consideration: in a democratic society it is fundamental to have respect toward differences of race, ethnicity, gender, sexual orientation and physical appearance, without abandoning every segment to its own luck, but questioning the relationships of power that create hierarchy among different positions. In what concerns physical-sporting activities, it is necessary to take into consideration the patriarchalism, present in conduction and administration of sport. In Brazil, a few black women have overpassed barriers, by using tools of their own culture to succeed as icons of sport. The goal of this study is to present some black athletes of high level who, by their trajectory, show us critical points of resistance in the categories of gender, race, they have to overcome. Aída dos Santos, Eliane Pereira, Elisângela Maria Adriano, Delma Gonçalves, Solange Chagas do Vale and Daiane dos Santos show us that the color of their skin has discriminated them, more in some modalities than in other, more for some athletes than for other. They also show us that discrimination is not determinative, in the sense that many of these athletes have made their way with their own feet, they have made agreements, they have won confidence and, most of all, they have conquered their dreams. They have been established themselves as points of reference in their fight in sports of high level, independently of their racial characteristics.
Keywords: gender; race; sport.